French and English language imperialism in the light of Gobard's tetraglossic theory of language alienation with special reference to Afrikaans, Flemish and Walloon language identity - Gijsen, Johan (Stellenbosch : Stellenbosch University, 2012)
Thesis (DLitt) -- University of Stellenbosch, 1995.